RNAi therapeutics: an antiviral strategy for human infections. (October 2020) - Kelleher, Anthony D; Cortez-Jugo, Christina; Cavalieri, Francesca; Qu, Yijiao; Glanville, Allan R; Caruso, Frank; Symonds, Geoff; Ahlenstiel, Chantelle L
Highlights: RNAi is a promising antiviral development strategy. Pathways include classic RNAi (mRNA target) and novel RNAi (promoter target). Most RNAi therapeutics act via transient, classical RNAi (cytoplasmic). Chronic human virus infections benefit from heritable, novel RNAi (nuclear). Delivery of RNAi therapeutics is enhanced using nanocarriers. Abstract : Gene silencing induced by RNAi represents a promising antiviral development strategy. This review will summarise the current state of RNAi therapeutics for treating acute and chronic human virus infections. The gene silencing pathways exploited by RNAi therapeutics will be described and include both classic RNAi, inducing cytoplasmic mRNA degradation post-transcription and novel RNAi, mediating epigenetic modifications at the transcription level in the nucleus. Finally, the challenge of delivering gene modifications via RNAi will be discussed, along with the unique characteristics of respiratory versus systemic administration routes to highlight recent advances and future potential of RNAi antiviral treatment strategies.